2004
DOI: 10.1590/s1678-97412004000300004
|View full text |Cite
|
Sign up to set email alerts
|

<![CDATA[<b>Should the Bidirectional Glenn Operation be performed with or without cardiopulmonary bypass?</b>]]>

Abstract: Objective: To compare patients who underwent the Bidirectional Glenn Operation with and without cardiopulmonary bypass (CPB), analyzing the characteristics and confirming if there is superiority of either of the employed techniques. patients with complex heart defects were submitted to this operative technique. The mean age of the patients was 19 months and 14 were female. The patients were divided into two groups: Group A with 7 patients (using CPB) and group B with 9 patients (without the use of CPB). Gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
2
4
0
Order By: Relevance
“…The early postoperative complications in our study were similar to those reported by Kogon et al, 10 Talwar et al, 8 Lapar et al, 7 Crotti et al, 26 and Lamberti et al 21 However the incidence of chylothorax was low in our study group. It could be because of the careful dissection carried out during the surgery.…”
Section: Discussionsupporting
confidence: 90%
“…The early postoperative complications in our study were similar to those reported by Kogon et al, 10 Talwar et al, 8 Lapar et al, 7 Crotti et al, 26 and Lamberti et al 21 However the incidence of chylothorax was low in our study group. It could be because of the careful dissection carried out during the surgery.…”
Section: Discussionsupporting
confidence: 90%
“…Croti et al prospectively compared BDG with and without CPB in a cohort of 16 patients. No neurological complications or pleural or pericardial effusions were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies exist on off‐CPB BDG and even fewer studies compare off‐CPB and on‐CPB BDG in a prospective manner . We performed this study to evaluate the potential benefits of off‐pump BDG and to compare the neurological outcomes as compared to BDG on CPB.…”
Section: Introductionmentioning
confidence: 99%
“…Croti et al compared 16 patients undergoing BDG with and without CPB and concluded that both techniques provide similar results with respect to morbidity and mortality, if the anatomic findings are appropriate and there is no severe hypoxia.…”
Section: Discussionmentioning
confidence: 99%